New possibilities of quality regulation for ceramic products - Malaiškiene, Jurgita; Mačiulaitis, Romualdas (Journal of Civil Engineering and Management, 2004)
Investigation of ceramic products is presented in the article. Material mix of these products consists of such components as clay of Rokai deposit, sand of Daugeliai deposit, crushed brick of Rokai brickworks, anthracite of Archangelsk region, peat of Rekyva’s deposit and ground bottle glass. Statistical regression analysis is performed for the measured structural parameters of a ceramic body and various components of material mix. Empirical equations are derived allowing to select the composition of material mix according to the desirable structural parameters of a ceramic article (reserve of pore volume, degree of structural in homogeneity, maximum rate of capillary wetting front, capillary rate of mass flow and total open porosity). After selecting the composition of material mix, the prognosis of ceramic body characteristics is performed. Results of the investigation will have a wide practical application. First Published Online: 14 Oct 2010